Adsorption and release studies of new cephalosporin from chitosan-g-poly(glycidyl methacrylate) microparticles. (September 2016) - Cigu, Toni Andor; Vasiliu, Silvia; Racovita, Stefania; Lionte, Catalina; Sunel, Valeriu; Popa, Marcel; Cheptea, Corina
Graphical abstract: Highlights: A new type of porous microparticles was investigated for cephalosporin adsorption. It was synthesized a new cephalosporin derivative. The kinetics, isotherm and thermodynamics of the cephalosporin were investigated. The pore diffusion and film diffusion coefficients were calculated. The drug release process was found to be controlled by diffusion. Abstract: Porous microparticles of chitosan- g -poly(glycidyl methacrylate) were obtained by grafting chitosan onto crosslinked networks based on glycidyl methacrylate and ethylene glycol dimethacrylate using suspension polymerization technique. A new cephalosporin from the indazole class prepared by acylation of 7-Aminodesacetoxycephalosporanic acid with mixed anhydride of 5-nitroindazole-1-yl-acetic acid was used as active principle. The cephalosporin-microparticle systems were characterized by FT-IR spectroscopy, SEM and AFM analysis. Batch experiments were carried out to study the influence of initial drug concentration, temperature, contact time, drug:microparticles ratio and pH on the adsorption process of cephalosporin onto porous crosslinked microparticles. Two-parameter and three-parameter isotherm models were used to evaluate the adsorption equilibrium. The values of diffusion coefficients indicate that the cephalosporin adsorption onto microparticles was controlled by both film diffusion and pore diffusion mechanisms. The analysis of the kinetic data of the release process indicate that the release mechanism of cephalosporin from microparticles corresponds to the anomalous transport mechanism.